The International Criminal Court’s Gravity Jurisprudence at Ten - Margaret M. DeGuzman (Washington University Global Studies Law Review, 2013)
This Essay analyzes the Court’s early jurisprudence interpreting the gravity threshold for admissibility. It argues that the threshold, while useful in garnering support for ratification of the Rome Statute, now seems destined to play a minor role in determining the ICC’s reach. While there are multiple possible explanations for this development, an important doctrinal cause identified in the jurisprudence is that the gravity threshold for admissibility is in tension with the Rome Statute’s provisions regarding jurisdiction. At least with regard to the admissibility of cases, the judges have concluded that interpreting the gravity threshold to exclude certain types of defendants or crimes from the Court’s reach would amount to an impermissible revision of the Court’s jurisdiction. To avoid this outcome, the judges have developed a flexible multi-factor approach to the gravity threshold that enables them to justify admitting virtually any case within the Court’s jurisdiction. The Essay concludes by arguing that, in light of the tension between admissibility and jurisdiction, the judges are right to relegate the gravity threshold to a minor role in determining the cases the Court adjudicates. To the extent the judges seek to limit the ICC’s reach, they should do so by interpreting the Court’s jurisdictional provisions directly rather than through the back door of admissibility.
Keywords: ICC; International Criminal Court; gravity threshold; admissibility; jurisdiction